PENGARUH EKSTRAK UMBI BIDARA UPAS (Merremia mammosa (Lour) Hall.f ) TERHADAP PERTUMBUHAN Salmonella typhi - Lubis, Andri Akhiruddin; Fifendy, Mades; Fitriani, Vivi (STKIP PGRI Sumbar, 2013)
ABSTRACT Salmonella typhi is the bacteria that causes typhoid fever typhoid. Typhoid occur in the presence of bacterial infection Salmonella typhi. Bacterial infection control can be done by giving antibiotics, but the bacteria have a high level of resistance to antibiotics. Resistance of bacterial resistance to antibiotics caused an increased mortality rate. It is therefore necessary to find a new alternative antimicrobial drugs. Bidara upas (Merremia mammosa ( Lour ) Hall.f ) is a plant that has a role as an antimicrobial because it contains compounds like flavonoids, resins and bitter substances. The purpose of this to determine the effect of tuber extract bidara upas (Merremia mammosa ( Lour ) Hall.f ) on the growth of Salmonella typhi. The study was conducted from August to September 2013 in the Laboratory Kopertis X, Padang. Using a completely randomized design (CRD) with 6 treatments and 3 replications. Data were analyzed by of variance (ANOVA), and a further test of Least Significant Difference (LSD). The results showed each tuber extract treatment bidara upas provides growth inhibition against Salmonella typhi bacteria. Of the study concluded bidara tuber extract (Merremia mammosa ( Lour ) Hall.f ) can inhibit the growth of Salmonella typhi.